How should we describe, diagnose and observe the Barrett's esophagus? - Akın, Hakan; Aydın, Yücel (Turkish Journal of Gastroenterology, 2017)
Abstract Barrett's esophagus (BE) is one of the major complications of gastroesophageal reflux disease (GERD) commonly encountered in gastroenterology clinics. A consensus has not been achieved yet with respect to the definition of BE in published guidelines. It is advised to use the Prague classification and not to use the definition of short and long segments for the endoscopic standardization of BE. Undertaking biopsies with white-light endoscopy from each of the 4 quadrants at 2-cm intervals is the standard method for the diagnosis of BE. Because of the ability to perform targeted biopsies, the available data indicate that advanced endoscopic techniques may reduce the number of biopsies needed for diagnoses. In the presence of severe esophagitis along with BE, the biopsies should be taken after 8 weeks of PPI therapy. The evidence values of the suggestions about the surveillance requirements and surveillance frequencies are low because the available data mostly rely on retrospective studies. We suggest that all the patients with BE should be referred to specialized centers for surveillance in Turkey. Considering the additional risk factors of the patient, endoscopy surveillance intervals of the patients with BE without dysplasia should be in a range of 3-5 years and annual surveillance should be made in BE with low-grade dysplasia. In the presence of BE with high-grade dysplasia (HGD), the patients should be referred to specialized centers for treatment within 3 months at the latest. Cite this article as: Akın H, Aydın Y. How should we describe, diagnose and observe the Barrett's esophagus? Turk J Gastroenterol 2017;28(Suppl 1); S26-S30 Full Text Turkish